Optimalisasi Peran Kader Institusi Masyarakat Pedesaan Dalam Program KKBPK di Kelurahan Pulo Brayan Darat I - Amalina, Febriani; Dewi Kurniawati (CV. ITTC INDONESIA, 2023)
Based on the Presidential Regulation of the Republic of Indonesia Number 62 of 2010 concerning the Population and Family Planning Agency (BKKBN), BKKBN is a Non-Ministerial Government Institution under and responsible to the President. BKKBN has the duty and function to carry out population control and family planning as mandated in Article 56 of the above Law. In the context of population control and the implementation of family planning in the region, the local government forms the Regional Population and Family Planning Agency and has the smallest group of units at the village or sub-district level, namely the Rural Community Institution. Pulo Brayan Darat I is one of the villages in the East Medan sub-district with an area of 0.75 km² which is the village with the largest population of 21,148 people. Pulo Brayan Darat I is the villages with the largest number of PUS with a low rate of achievement of family planning participation. This is the main issue that needs more research and attention.